2019
DOI: 10.1186/s12885-019-5377-y
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent response of daunorubicin on cytotoxicity, cell cycle and DNA repair in acute lymphoblastic leukaemia

Abstract: Background Daunorubicin is commonly used in the treatment of acute lymphoblastic leukaemia (ALL). The aim of this study was to explore the kinetics of double strand break (DSB) formation of three ALL cell lines following exposure to daunorubicin and to investigate the effects of daunorubicin on the cell cycle and the protein kinases involved in specific checkpoints following DNA damage and recovery periods. Methods Three ALL cell lines CCRF-CEM and MOLT-4 derived from T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 50 publications
5
37
0
Order By: Relevance
“…Interestingly, our results also indicate that HK-II inhibition using 3-BP results in substantial decrease in the K-562 cell proliferation through the induction of S-phase (4 h) and G 2 -M phase cell cycle arrest (24 h) augmented by the DNR in the CT (Figure 4). DNR induced cell cycle arrest in G 2 /M phase has been reported in cancer cells including acute myeloid leukemic cells [48]. However, data presented here suggest that the combined DNR and 3-BP treatment leads to profound accumulation of cells in both S phase and G 2 /M phase resulting in significantly higher growth delay.…”
Section: Discussionmentioning
confidence: 44%
“…Interestingly, our results also indicate that HK-II inhibition using 3-BP results in substantial decrease in the K-562 cell proliferation through the induction of S-phase (4 h) and G 2 -M phase cell cycle arrest (24 h) augmented by the DNR in the CT (Figure 4). DNR induced cell cycle arrest in G 2 /M phase has been reported in cancer cells including acute myeloid leukemic cells [48]. However, data presented here suggest that the combined DNR and 3-BP treatment leads to profound accumulation of cells in both S phase and G 2 /M phase resulting in significantly higher growth delay.…”
Section: Discussionmentioning
confidence: 44%
“…DNR is an anthracycline chemotherapeutic drug that inhibits DNA and DNA-dependent RNA synthesis ( 22 ), and has been extensively used in the treatment of leukemia. Moreover, DNR is a non-specific cell cycle agent, and thus exerts cytotoxic effects at every phase of the cell cycle, including G 0 , G 1 , S, G 2 and M ( 23 ). The results of the present study suggested that low CREBBP expression potentially resulted in DNR chemoresistance via regulation of cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Both daunorubicin and doxorubicin have an anthracyclic plane, which can be inserted between DNA base pairs and tightly bound to DNA, becoming an obstacle of DNA spatial structure, thus inhibiting DNA and DNA-dependent RNA synthesis, and can selectively act on purine nucleosides [13]. At the same time, with the effects of cytotoxicity, daunorubicin and doxorubicin can also inhibit the activity of nuclear topoisomerase, interfere with the DNA fracture-reconnection reaction caused by topoisomerase, leading to DNA double strand break, as well as DNA single strand break [14]. Mitomycin has anticancer effect on a variety of cancers, also works as a non-specific drug in cell cycle [15].…”
Section: Definition and Classification Of Anticancer Antibioticsmentioning
confidence: 99%